2018
DOI: 10.1021/acsami.8b17590
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of rGO/g-C3N4/CNT Microspheres via an Ethanol-Assisted Spray-Drying Method for High-Performance Lithium–Sulfur Batteries

Abstract: rGO/g-C 3 N 4 and rGO/g-C 3 N 4 /CNT microspheres are synthesized through the simple ethanol-assisted spray-drying method. The ethanol, as the additive, changes the structure of the rGO/g-C 3 N 4 or rGO/g-C 3 N 4 /CNT composite from sheet clusters to regular microspheres. In the microspheres, the pores formed by reduced graphene oxide (rGO), g-C 3 N 4 , and carbon nanotube (CNT) stacking provide physical confinement for lithium polysulfides (LiPSs). In addition, enriched nitrogen (N) atoms of g-C 3 N 4 offer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 62 publications
1
45
0
Order By: Relevance
“…The nitrogen content of HNCM700, HNCM800, and HNCM900 are up to 18.28, 12.43, and 7.05 at%, which are higher than that of N‐CNTs (4.99 at%, Table S2, Supporting Information). The C 1s spectra (Figure e) can be deconvoluted to three main peaks centered at about 284.8, 286.1, and 288.7 eV, corresponding to CC, CO, and CN bonding . HNCM700 possess the highest CN level among the four materials, indicating the highest N‐doping content.…”
Section: Resultsmentioning
confidence: 99%
“…The nitrogen content of HNCM700, HNCM800, and HNCM900 are up to 18.28, 12.43, and 7.05 at%, which are higher than that of N‐CNTs (4.99 at%, Table S2, Supporting Information). The C 1s spectra (Figure e) can be deconvoluted to three main peaks centered at about 284.8, 286.1, and 288.7 eV, corresponding to CC, CO, and CN bonding . HNCM700 possess the highest CN level among the four materials, indicating the highest N‐doping content.…”
Section: Resultsmentioning
confidence: 99%
“…reported the synthesis of a GO/g-C 3 N 4 microsphere by an ethanol-assisted spray drying approach [112]. Zhang et al also reported the design of a sponge-like free-standing 3D S/graphene@g-C 3 N 4 hybrid using a microemulsion-assisted assembly method (Fig.…”
Section: Other Composite Fabrication Strategiesmentioning
confidence: 99%
“…However, they are difficult to achieve high areal sulfur‐loading cathodes and suffer from complex preparation methods. [ 19 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%